PhyloQuant approach provides insights into Trypanosoma cruzi evolution using a systems-wide mass spectrometry-based quantitative protein profile - Simon Ngao Mule (Nature Portfolio, 2021)
Simon Ngao Mule et al. introduce the “PhyloQuant” approach to infer evolutionary relationships of organisms, focusing on the genetically diverse Trypanosoma cruzi strains based on protein expression profiles derived from mass spectrometry. The authors show that phylogenies constructed from their PhyloQuant method and traditional molecular phylogenies are significantly correlated, and demonstrate species-specific proteins and their differential expression over evolutionary time.